The Impact of Work Facilities and Motivation Through Discipline on Employee Performance at the Community and Village Empowerment Service, West Tanjung Jabung Regency - Sofyan Ali; M. Zahari; Osrita Hapsara (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the influence of work facilities and motivation through discipline on employee performance at the Community and Village Empowerment Office of West Tanjung Jabung Regency. The problems raised in this study are the still limited work facilities, varying employee motivation due to the uneven distribution of Additional Employee Income (TPP), and employee discipline that is not fully optimal, thus impacting uneven performance achievements. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 51 respondents who are employees at the Community and Village Empowerment Service of West Tanjung Jabung Regency. Data analysis was carried out using validity, reliability, regression, and path analysis tests to examine the direct and indirect effects between variables. The results of the study indicate that (1) work facilities have a positive effect on employee discipline and performance; (2) motivation has a positive effect on employee discipline and performance, (3) work discipline has a positive effect on employee performance, and (4) work facilities and motivation have an indirect effect on employee performance through discipline. Thus, improving adequate work facilities, providing fair motivation, and consistently enforcing discipline will have a significant impact on improving employee performance.